Improving Flood Management, Prediction and Monitoring : Case Studies in Asia - Zulkifli Mohd. Yusop, editor 598922; Azmi Aris, editor 263408; Nor Eliza Alias, editor 630084; Kogila Vani Annammala, editor 614089; Waugh, William L., editor 646864; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, UK : Emerald Publishing Limited, 2018)
Flood risk management requires a multi-disciplinary approach with experts from the fields of health, town planning, civil engineering, computer science and mathematical statistics. This volume presents chapters highlighting the methodologies and tools developed to improve flood management and flood risk reduction. Chapters in this important volume consider research on emerging economies and developing countries and the case studies are focused on Malaysia, China and South-East Asia. The book presents key research from areas of the globe where flood management has not traditionally been studied but the effects of climate change and natural disasters present huge challenges for societies in the region. This volume, edited by leaders in the field of disaster management, would be of particular interest to students, researchers and policy specialists involved with examining flood-related risk reduction methods and systems for key decision makers